Inflammatory and oxidative stress markers in intracerebral hemorrhage: Relevance as prognostic markers for quantification of the edema volume. (28th June 2022) - Rendevski, Vladimir; Aleksovski, Boris; Mihajlovska Rendevska, Ana; Hadzi‐Petrushev, Nikola; Manusheva, Nensi; Shuntov, Blagoj; Gjorgoski, Icko
Abstract: We aimed to analyze the inflammatory and oxidative stress (OS) markers after intracerebral hemorrhage (ICH) and their temporal changes, interaction effects, and prognostic values as biomarkers for the prediction of the edema volume. Our prospective, longitudinal study included a cohort group of 73 conservatively treated patients with ICH, without hematoma expansion or intraventricular bleeding, which were initialized with the same treatment and provided with the same in‐hospital care during the disease course. Study procedures included multilevel comprehensive analyses of clinical and neuroimaging data, aligned with the exploration of 19 inflammatory and five OS markers. White blood cells (WBC), C‐reactive protein (CRP), erythrocyte sedimentation rate (ESR), neutrophilia, and lymphopenia peaked 3 days post‐ICH, and they showed much stronger correlations with clinical and neuroimaging variables, when compared to the admission values. An intricate interplay among inflammatory (WBC, CRP, neutrophils, neutrophil‐to‐lymphocyte ratio [NLR], interleukin (IL)‐6, and IL‐10) and OS mechanisms (catalase activity and advanced oxidation protein products [AOPP]) was detected operating 3‐days post‐ICH, being assessed as relevant for prediction of the edema. The overall results suggested complex pathology of formation of post‐ICH edema, via: (A) Not additive, but statistically significant synergistic interactions between CRP‐ESR, neutrophils‐CRP, and neutrophils‐IL‐6 as drivers for the edema formation; (B) Significant antagonistic effect of high protein oxidation on the CRP‐edema dependence, suggesting a mechanism of potential OS‐CRP negative feedback loop and redox inactivation of CRP. The final multiple regression model separated the third‐day variables NLR, CRP × AOPP, and WBC, as significant prognostic biomarkers for the prediction of the edema volume, with NLR being associated with the highest effect size. Our developed mathematical equation with 3D modeling for prediction and quantification of the edema volume might be beneficial for taking timely adequate strategies for prevention of delayed neurological deteriorations. Abstract : The complex formation of post‐ICH brain edema.